Effectiveness and quality of public health services: A case study from Ujoh Bilang, Indonesia - Sopya,; Syahrani,; Herman, (International Journal of Psychosocial Rehabilitation, 2020)
Until whenever, the health sector has always been a human need and the center of government attention to continuously improve its quality and quantity. Apart from education, this sector is fundamental to creating sustainable human development. The study examines and analyzes public health services carried out at the Puskesmas in Ujoh Bilang District, Mahakam Ulu Regency (Indonesia). In addition, we also identify supporting and inhibiting factors. This type of study is descriptive, based on a qualitative approach. We conclude that in public health services, service procedures are not organized and not optimal. The time needed by the community from registration to service takes more than 60 minutes. The duration of service is considered to be the main inhibiting factor, considering that the community health center is isolated, with minimal infrastructure and inadequate access to support. Supporting factors for services greatly affect public health (for example, support from the government) in terms of budget allocation, infrastructure, and medical personnel to support these activities. In addition, there are inhibiting factors, including the level of discipline of medical personnel and other supporting resources. The value of originality lies in the novelty of the study, which directly reveals problems related to health services for people in remote areas.